Cellular Microbiaxial Stretching Assay for Measurement and Characterization of the Anisotropic Mechanical Properties of Micropatterned Cells. Issue 2 (23rd February 2022) - Rothermel, Taylor M.; Cook, Bernard L.; Alford, Patrick W.
Abstract: Characterizing the mechanical properties of single cells is important for developing descriptive models of tissue mechanics and improving the understanding of mechanically driven cell processes. Standard methods for measuring single‐cell mechanical properties typically provide isotropic mechanical descriptions. However, many cells exhibit specialized geometries in vivo, with anisotropic cytoskeletal architectures reflective of their function, and are exposed to dynamic multiaxial loads, raising the need for more complete descriptions of their anisotropic mechanical properties under complex deformations. Here, we describe the cellular microbiaxial stretching (CμBS) assay in which controlled deformations are applied to micropatterned cells while simultaneously measuring cell stress. CμBS utilizes a set of linear actuators to apply tensile or compressive, short‐ or long‐term deformations to cells micropatterned on a fluorescent bead‐doped polyacrylamide gel. Using traction force microscopy principles and the known geometry of the cell and the mechanical properties of the underlying gel, we calculate the stress within the cell to formulate stress‐strain curves that can be further used to create mechanical descriptions of the cells, such as strain energy density functions. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Assembly of CμBS stretching constructs Basic Protocol 2 : Polymerization of micropatterned, bead‐doped polyacrylamide gel on an elastomer membrane Support Protocol : Cell culture and seeding onto CμBS constructs Basic Protocol 3 : Implementing CμBS stretching protocols and traction force microscopy Basic Protocol 4 : Data analysis and cell stress measurements